Characterization and application of PBA fiber optic chemical film sensor based on fluorescence multiple quenching - 陈坚 李伟 阎超 袁立懋 郭炬亮 周新继 (Science China. Life sciences, 1997)
The three types of structure of the pyrenebutyric acid of fiber optic chemical film sensor were stud-ied by fluorescence multiple quenching. They are, for different test samples and purposes, respectively general, three-way and combined. A tri-cup method was designed to demonstrate the multiple quenching of response mechanism, and a relationship formula of mathematical approach was established. The response mechanism was shown to include the dynamic quenching , inner-filter effects and/or resonance energy transfer. To show the response characterization in a series of organic and inorganic quenchers, a new concept of apparent quenching coefficient Kq was advanced. This kind of sensor has been used in continuous and in situ monitoring of the dissolution rate of drug tablets, on line and in situ monitoring of some organic therapeutic drugs in biological fluid and Cr( VI ) in industrial waste water. The measured data were examined and compared with HPLC or HPTLCS. Test results show that the sensors and appa